Just schools : a whole school approach to restorative justice - Hopkins, Belinda, 1956- (Jessica Kingsley, 2004)
Restorative justice is a dynamic and innovative way of dealing with conflict in schools, promoting understanding and healing over assigning blame or dispensing punishment. It can improve the quality of school life not only through conflict resolution, but also in terms of developing active citizenship skills, good self-esteem, open communication and team work in students. Belinda Hopkins is at the forefront of the development of restorative justice in the UK, and in this practical handbook she presents a whole school approach to repairing harm using a variety of means including peer mediation.